Purification and characterization of a protease from Clostridium botulinum type A that nicks single-chain type A botulinum neurotoxin into the di-chain form. - Dekleva, M L (1990)
A protease that nicks the approximately 150-kilodalton (kDa) single-chain type A botulinum neurotoxin into the approximately 150-kDa di-chain form in vitro was isolated from Clostridium botulinum type A (Hall strain) cultures. The di-chain neurotoxin generated in vitro is composed of an approximately 50-kDa light chain and an approximately 100-kDa heavy chain which are disulfide linked and is indistinguishable from the di-chain neurotoxin that forms in vivo and is routinely isolated (M.L. Dekleva and B.R. DasGupta, Biochem. Biophys. Res. Commun. 162:767-772, 1989). This enzyme was purified greater than 1,000-fold by ammonium sulfate precipitation, QAE-Sephadex Q-50, Sephadex G-100, and CM-Sephadex C-50 chromatography steps with the synthetic substrate N-benzoyl-DL-arginine-p-nitroanilide. The approximately 62-kDa amidase (protease) is a complex of 15.5- and 48-kDa polypeptides (determined by polyacrylamide gel electrophoresis) that could not be separated without sodium dodecyl sulfate. The enzyme has an isoelectric point of pH 5.73, a pH optimum of 6.2 to 6.4, an absolute requirement for a thiol-reducing agent as well as a divalent metallic cation (probably Ca2+) for activity, and a temperature optimum of 70 degrees C. Tests with several synthetic substrates indicated the high specificity of the enzyme for arginyl amide bonds.